Peran Dinas Koperasi dan UKM Kabupaten Karawang dalam Meningkatkan Kompetensi Digital bagi Pelaku Usaha Mikro, Kecil dan Menengah - Melly Maryana; Wanta Wanta; Dwi Epty Hidayaty (Pusat Riset dan Inovasi Nasional, 2024)
Digitalization is an important factor in increasing the competitiveness of MSMEs, considering that in the city of Karawang there are still many MSMEs that are not yet digital tend to be left behind in terms of innovation and market access, so there is a risk of experiencing a decrease in competitiveness. So that the Karawang Regency Cooperatives and MSMEs Office has a strategic role in supporting the digital transformation of MSME actors. This research aims to analyze the role of the Cooperative Office and its effectiveness in improving the digital competence of MSME actors, as well as identify obstacles and sustainability strategies in the implementation of digitalization programs. The research method used is a qualitative approach with conclusions drawn that are validated through triangulation of sources. The results of the study show that the Karawang Regency Cooperatives and MSMEs Office has an important role in designing a digitalization training program, the program has a significant impact in improving the digital competence of MSME actors. The main obstacle faced is the limited understanding of technology among some MSME actors, especially those who are older or who are not used to using digital devices. Therefore, the Karawang Regency Cooperatives and SMEs Office is expected to continue to innovate in designing and implementing a more inclusive and comprehensive digitalization training program.